2010
DOI: 10.1139/t09-138
|View full text |Cite
|
Sign up to set email alerts
|

Volume change behaviour of a compacted scaly clay during cyclic suction changes

Abstract: The research presented in this paper focuses on the investigation and modelling of the volume change response of compacted tectonised clay samples subjected to several wetting and drying cycles in controlled-suction oedometers.\ud Oedometer tests were carried out under different values of constant vertical net stress, and wetting and drying cycles were performed varying applied matric suction between 10 and 800 kPa. The investigation was complemented with a study of the material microstructure to support the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…The majority of the accumulated volumetric strain occurs during the first wetting-drying cycle. As summarized earlier in the text, similar phenomena have been confirmed by many other experimental studies performed by Dif and Bluemel (1991), Day (1994), Al-Homoud et al (1995), Basma et al (1996), Alonso et al (2005), Nowamooz and Masrouri (2008), and Airò Farulla et al (2010).…”
Section: Two Swelling-shrinkage Strain Componentssupporting
confidence: 86%
See 3 more Smart Citations
“…The majority of the accumulated volumetric strain occurs during the first wetting-drying cycle. As summarized earlier in the text, similar phenomena have been confirmed by many other experimental studies performed by Dif and Bluemel (1991), Day (1994), Al-Homoud et al (1995), Basma et al (1996), Alonso et al (2005), Nowamooz and Masrouri (2008), and Airò Farulla et al (2010).…”
Section: Two Swelling-shrinkage Strain Componentssupporting
confidence: 86%
“…The postulation that the aggregate deformation is reversible can be confirmed directly by digital image analysis of environmental scanning electronic microscope (ESEM) micrographs, in which the volume change of aggregates can be extracted. Romero and Simms (2008) and Airò Farulla et al (2010) have reported that the aggregate deformation shows good reversibility by this method. Besides the elastic-like behavior of aggregates under loading, the aggregates with unstable structure may break down.…”
Section: Theoretical Backgroundmentioning
confidence: 85%
See 2 more Smart Citations
“…The specimens were obtained by dynamically compacting clay lumps that were partially disaggregated (passing them through a 4.25 mm sieve), previously air-dried, and subsequently prepared to target water content values (Ferrari 2007). The compaction took place on the dry side of optimum, providing specimens that are characterized by a double-structured microfabric arrangement (Airò Farulla et al 2010). The effect of suction variations on the volumetric behaviour at the microstructural level was examined using environmental scanning electron microscopy (ESEM) photomicrographs (Airò Farulla et al 2010).…”
Section: Experimental Results On a Clayey Soilmentioning
confidence: 99%